Exploring the needs of family caregivers: preliminary findings - Othman, Hamidah; Mohamed Ludin, Salizar (2018)
Background: Family caregivers play an important role at home during the rehabilitation phase of severe traumatic brain injury survivor. Understand the survivor’s needs was the most crucial thing to focus on. The purpose of this study is to explore the needs of family caregivers towards the care of sTBI survivor at home.